Ethno-Edutainment Electronic Module (EMEE) to Strengthen Local Cultural Character in Elementary School Students - Titin Sunaryati; Muhamad Fatchan; Muhamad Sudharsono; Pipin Angela (LJPI UI Bunga Bangsa Cirebon, 2025)
The erosion of local cultural values due to globalization poses a significant challenge to the development of character in Indonesian students, who are expected to uphold tolerance, ethics, and mutual respect. Objective: This study aims to develop an Android-based ethno-edutainment electronic module to strengthen local cultural character among elementary school students. Novelty: The module integrates ethno-edutainment and local cultural values into a digital learning platform, offering an innovative approach to character education. Methods: The module was developed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) within a Research and Development (R&D) framework. The product was validated by media, content, and language experts, and tested on 55 students at Pondok Bambu 06 Duren Sawit State Elementary School, East Jakarta. Results: The validation results showed that the module was categorized as